2008
DOI: 10.1099/vir.0.2008/001933-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a novel adult diarrhoea rotavirus strain J19 isolated in China and its significance for the evolution and origin of group B rotaviruses

Abstract: The complete genome of a novel adult diarrhoea rotavirus strain J19 was cloned and sequenced using an improved single-primer sequence-independent method. The complete genome is 17 961 bp and is . Northern blot analysis and genomic sequence analysis indicated that segments 1-11 encode 11 viral proteins, respectively. Protein alignments with the corresponding proteins of J19 with B219, and groups A, B and C rotaviruses, produced higher per cent sequence identities to B219. Among groups A, B and C rotaviruses, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 37 publications
2
31
0
1
Order By: Relevance
“…So far, nucleotide sequences are available only for group A, B, and C rotaviruses. Phylogenetic analysis of the sequences confirmed the suggested grouping of these viruses (30,31,69,74). In addition, group-specific conserved sequences are present at the termini of the genome segments.…”
supporting
confidence: 49%
See 2 more Smart Citations
“…So far, nucleotide sequences are available only for group A, B, and C rotaviruses. Phylogenetic analysis of the sequences confirmed the suggested grouping of these viruses (30,31,69,74). In addition, group-specific conserved sequences are present at the termini of the genome segments.…”
supporting
confidence: 49%
“…In addition, several group A, B, and C rotaviruses have been characterized on the basis of their genome sequences, allowing a deeper insight into the evolutionary relationship of these viruses (1,31,42,43). The first genome sequence of the group D rotavirus presented here enables a more comprehensive classification of this virus compared to its former grouping based on serological criteria and limited terminal fingerprinting analysis (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the sequences of GBR strains showed that nucleotide sequence identity of MP-1 isolate of HuGBR was very high with Bang373 and CAL-1 (98.6 and 97.7%, respectively) and amino acid identity more than 93% with Bang373 and CAL-1 strains. The nucleotide and amino acid sequence identities with Chinese ADRV (WH-1) strain isolated in 2002 from Wuhan [24] was 92.8 and 92.5%, respectively, while identities with another Chinese ADRV strain (J19) [11] was considerably lower (45.6 and 48.3%, respectively). The sequences among Indian (MP-1 and CAL-1) and Bangladeshi (Bang 373) strains were more conserved, while point mutations were observed at several nucleotide positions (63, 66, 72, 76, 87, 144, 151 and 155) in ADRV (WH-1) strain, with change in amino acid at 26 (amino acid changed from V to I) and at 51 (amino acid changed from S to A) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Dentro do grupo A, são observados elevados níveis de diversidade com alguns genes apresentando-se mais conservados que outros (JIANG et al, 2008).…”
Section: Evolução Viralunclassified